Toponymy and Collective Memory: Tracing the History of Sukarara Village Through Oral Traditions and Naming of Weaving Ornamental Varieties - Fahimah Saifuddin (Civiliza Publishing, Indonesia., 2026)
Sukarara Village in Central Lombok has been better known as a weaving tourist destination, while the history behind the name of the village itself is rarely known. This research aims to trace the origin of the name Sukarara Village (toponymy) and the philosophical meaning of the traditional weaving ornamental variety that has been passed down from generation to generation, by considering that both were born from the same process, namely the collective memory of the community that was passed down orally without inscriptions or official written archives. This research uses a descriptive qualitative method with an ethnographic approach, through in-depth interviews with traditional leaders and weaving artisans, participatory observation, and the study of local historical documents. The results of the study show that the name